2021
DOI: 10.1108/oir-01-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

The role of social influencers for effective public health communication

Abstract: PurposeThe purpose of the study is to explore the suitability of social media influencers (SMIs) for communicating public health messages via social media platforms. The study identifies key persuasive communication components that influence individuals' attitudes and, subsequently, intentions to follow health-related information shared by SMIs.Design/methodology/approachQualitative interviews with healthcare workers and interactions with 332 active social media users via structured online questionnaires were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 75 publications
3
11
0
1
Order By: Relevance
“…We also suggest that it would be useful to encourage health officials to actively leverage social media users' willingness to engage in these topics by disseminating content that invites audiences to engage in conversations. In this respect, we concur with Gupta et al . (2021) that communicating public health messages through social media has represented a missed opportunity for health agencies given the lack of resourcing and competency in using these mechanisms for dynamic communication with the public.…”
Section: Practical Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…We also suggest that it would be useful to encourage health officials to actively leverage social media users' willingness to engage in these topics by disseminating content that invites audiences to engage in conversations. In this respect, we concur with Gupta et al . (2021) that communicating public health messages through social media has represented a missed opportunity for health agencies given the lack of resourcing and competency in using these mechanisms for dynamic communication with the public.…”
Section: Practical Implicationssupporting
confidence: 93%
“…We also suggest that it would be useful to encourage health officials to actively leverage social media users' willingness to engage in these topics by disseminating content that invites audiences to engage in conversations. In this respect, we concur with Gupta et al (2021) that communicating public health messages through social media has represented a missed opportunity for health agencies given the lack of resourcing and competency in using these mechanisms for dynamic communication with the public. Moreover, when elevating authoritative health advice, it would be preferable to clearly delineate the basis of knowledge informing this advice from government decision-making to enable users of social media to explore any evidence as distinct from the potential responses enacted by the polity.…”
Section: Practical Implicationssupporting
confidence: 79%
“…Increasingly, social media influencers and independent video creators have been found to have an outsized influence on the dissemination of health information online. [23][24][25] Indeed, in our study, none of the top 100 videos were uploaded by corporations, health organizations, for-profit entities, or non-profit entities, and only 11% of videos were uploaded by HCPs. This limited presence of HCPs on TikTok has been observed in other studies as well.…”
Section: Discussionmentioning
confidence: 64%
“…In order to counteract the action of ‘misinformation influencers’, healthcare influencers have been suggested to play a relevant role in debunking myths and conspiracy theories, as well as providing access to valuable and accurate information for their followers and beyond 8. In addition, it has been shown that influencers may play a relevant role in public health communication amid a health crisis 56. WHO has therefore been interested in supporting healthcare influencers to promote evidence-based messages about COVID-19 and vaccines through various social media platforms 57.…”
Section: Project Fides: a Community Of Healthcare Influencers Fightin...mentioning
confidence: 99%
“… 8 In addition, it has been shown that influencers may play a relevant role in public health communication amid a health crisis. 56 WHO has therefore been interested in supporting healthcare influencers to promote evidence-based messages about COVID-19 and vaccines through various social media platforms. 57 Influencers can, in fact, adopt the most appropriate communication strategy for their niche of followers, thus allowing for a detailed personalisation of public health messages, in line with what has been proposed in a recent ethics and communication framework to deal with public health emergencies.…”
Section: Project Fides: a Community Of Healthcare Influencers Fightin...mentioning
confidence: 99%